The implementation of the problem-based learning model to improve learning outcomes in static electricity - Sopiatunisa (Research in Physics Education, 2024)
Low student learning activity impacts their academic achievement, which tends to be low or results in poor learning outcomes. To address this issue, the researcher examined one instructional model, namely Problem-Based Learning. This study implemented PBL in the context of physics learning to improve students' learning outcomes on the topic of static electricity. The research employed a quantitative method with a Control Group Pretest-Post-test Design. The participants were ninth-grade high school students, where the control class received a lecture-based method, while the experimental class used the Problem-Based Learning model. The average pretest and post-test scores in the experimental class increased from 6.32 to 10.72, reflecting a 70% improvement, with significant changes observed in the learning process. Similarly, students’ learning outcomes in the conventional lecture-based learning model also improved. The average pretest and post-test scores increased from 6.32 to 7.60, showing a 20% improvement. The percentage comparison of the average post-test scores between the experimental and control classes was 41%. The experimental group was categorized as having a moderate improvement, indicating that the Problem-Based Learning model had a moderate effect on learning outcomes. Meanwhile, the control group was categorized as having a low improvement, showing that the lecture method had a low effect on students’ learning outcomes.